An efficient fatigue analysis for the nonbonded flexible riser. (3rd October 2022) - Li, Pengjie; Dai, Tianjiao; Jin, Xing; Dong, Leilei; Liu, Shuaiqi; Yang, Shuo; Xiang, Xianbo; Kang, Hooi-Siang
ABSTRACT: This paper presents an efficient fatigue analysis for the non-bonded flexible riser. This fatigue analysis is based on well approved methodology including stochastic analysis of sea states, global response analysis of riser and local stress analysis of individual tensile wires followed by rain flow and Palmgren-Miner methods for calculating the fatigue damage and fatigue life. For the global response analysis, the nonlinear hysteresis relationship between bending moment and curvature of riser is coupled for accurately allocating the bending stiffness in the corresponding curvature range. For the local stress analysis, the simplified bending moment model is applied for describing the stick-slip behavior, which is efficient for calculating axial stress of individual tensile wires when 3D effects along the pipe is not considered. Sensitivity studies with respect to the flooded condition of tensile annulus layer and friction coefficient are further carried out for investigating the associated effects on the fatigue life.